Perbandingan Hukum Perjanjian Menurut Sistem Hukum Civil Law dan Common Law: Suatu Perbandingan Antara Indonesia dan Amerika - Portuna, Caroline Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
A legal system is a collection of rules that regulate society or government within a particular country. Each country has its own legal system to govern its administration, including Indonesia. Comparative civil law is an effort to study and analyze the differences and similarities in civil law systems across various countries. By comparing laws, we can understand the worldview and legal systems of other nations. The research method used in this study is the juridical-normative method, employing a statute approach and a comparative approach. The legal systems of Indonesia and the United States have different approaches to regulating contract law. Despite the differences in specific regulations, both legal systems aim to provide a clear and fair framework for the formation and enforcement of contracts. General principles such as freedom of contract, propriety, and legal certainty serve as the foundation of each legal system.